SOME DEBATES OF HERMENEUTIC AND LEGAL INTERPRETATION: CRITICAL ANALYSIS OF HANS-GEORG GADAMER PHILOSOPHICAL HERMENEUTICS - Silalahi, Artha Debora (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract Gadamer’s philosophical hermeneutics is rooted in the idea that interpretation, understanding, or meaning cannot take place outside of historical and social contexts. This approach challenges the traditional view of law as an autonomous and rational discourse, emphasizing the importance of dialogue and ethical deliberation in legal interpretation. Gadamer’s insights provide a unique perspective on legal hermeneutics, offering necessary protocols for determining, giving meaning, and emphasizing the historical and social embeddedness of legal practice. While some describe legal interpretivism as a hybrid between legal positivism and natural law theory, Gadamer’s hermeneutics offers an alternative approach to legal meaning, focusing on the historical and social contexts that shape interpretive activities. This approach provides a nuanced understanding of legal interpretation, emphasizing the concretization of the law through dialogue and ethical deliberation. Abstrak Hermeneutika filosofis Gadamer didasarkan pada asumsi bahwa penafsiran, pemahaman, atau makna tidak dapat muncul di luar konteks sejarah dan sosial. Pendekatan ini menantang pandangan tradisional tentang hukum sebagai wacana yang otonom dan rasional serta menyoroti pentingnya dialog dan pertimbangan etis dalam penafsiran hukum. Gagasan Gadamer memberikan perspektif unik mengenai hermeneutika hukum dengan menyarankan protocol yang diperlukan untuk menentukan makna dan menyoroti interkoneksi historis dan sosial dari praktik hukum. Meskipun ada yang menggambarkan interpretasi hukum sebagai kombinasi positivisme hukum dan teori hukum kodrat, hermeneutika Gadamer menawarkan pendekatan alternatif terhadap makna hukum dengan berfokus pada konteks sejarah dan sosial yang membentuk aktivitas hukum. Pendekatan ini memungkinkan adanya pemahaman yang berbeda mengenai penafsiran hukum dengan penekanan pada penerapan hukum melalui dialog dan pertimbangan etis.